dfLet [tex]f(x)=\sec x[/tex] and [tex]g(x)=\sqrt x[/tex]. Then
[tex]y=\sec\sqrt x=\sec(g(x))=f(g(x))=f\circ g(x)[/tex]
By the chain rule,
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\mathrm dy}{\mathrm du}\dfrac{\mathrm du}{\mathrm dx}[/tex]
where [tex]u=g(x)=\sqrt x[/tex], so that [tex]y=f(g(x))=f(u)=\sec u[/tex]. We have
[tex]\dfrac{\mathrm du}{\mathrm dx}=\dfrac1{2\sqrt x}[/tex]
[tex]\dfrac{\mathrm d\sec u}{\mathrm du}=\sec u\tan u[/tex]
and so
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\sec u\tan u\dfrac{\mathrm dy}{\mathrm du}=\dfrac{\sec\sqrt x\,\tan\sqrt x}{2\sqrt x}[/tex]